Revitalisasi Literasi Membaca dan Menulis sebagai Strategi Pembelajaran Bahasa Indonesia di SMK Menghadapi Tantangan Abad 21 - Pontjowulan, Pontjowulan (PT Literasi Nusantara Publisher, 2025)
Reading and writing literacy skills are fundamental in Indonesian language learning, particularly in Vocational High Schools that are facing the challenges of the 21st century. However, the reality shows that students’ literacy levels remain low, as indicated by limited reading interest, weak critical thinking skills, and a lack of systematic and reflective writing abilities. This study aims to examine strategies for revitalizing reading and writing literacy in Indonesian language instruction at SMKs through a literature review method. Data were collected from scholarly literature, educational policy documents, and recent relevant research, and analyzed using content analysis. The findings indicate that literacy revitalization can be carried out through the use of authentic texts in teaching, digital technology integration, problem-based literacy projects, and the collaborative strengthening of school literacy culture. Literacy is not only an indicator of language learning success but also a foundation for 21st-century competencies, including critical thinking, communication, and creativity. Therefore, revitalizing literacy becomes a key strategy in shaping SMK graduates to be adaptive, productive, and prepared to face global challenges.